Balanced scorecard recontruction through value of Khalifatullah fil Ardh – Abdullah - Diana Nurindrasari; Iwan Triyuwono; Aji Dedi Mulawarman (Universitas Hayam Wuruk Perbanas, 2018)
This study aims to reconstruct the basis and perspective on the balanced scorecard. The basic assumptions and perspectives in the balanced scorecard only prioritize material aspects. Yet, Â the reality of a performance is also influenced by non-material aspects such as the existence of God, society, and the environment. Therefore, it shows an imbalance. The reconstruction is done by using the values contained in the qiyam. This research was conducted in two main stages, namely conducting a literature study on the fundamentals and perspectives on the balanced scorecard. Then, the values in the qiyam are synchronized to produce a new balanced scorecard construct. The results of the reconstruction show the goals and perspectives of a more complete and sustainable performance measurement through the basic concepts of responsibility and trust in the dimensions of Khalifatullah fil ard and Abdullah. The performance measurement is intended to fulfill the mandate to God, the universe, and fellow humans. The formulation of performance measurement objectives produces new perspectives: Â human resources, business processes, distribution, environment, and society. The reconstruction of the balanced scorecard contributes to the managerial side of the company in drawing up the company's performance measurement framework. The results of this study can also be used as the development of knowledge in academics, especially accounting and management.